Kredit Bermasalah, Dana Pihak Ketiga, Biaya Operasional, Pendapatan Operasional dan Profitabilitas di Lembaga Perkreditan Desa - Yuni, Ni Wayan Asri; Sujana, I Ketut (E-Jurnal Akuntansi, 2022)
The study aims to determine the effect of non-performing loans, third party funds, and operational income operating costs on profitability in Village Credit Institutions (LPD) throughout Ubud district. The population in this study were all LPDs in the entire District of Ubud, totaling 32 LPDs. The sampling technique used is saturated sampling. The data obtained were analyzed using multiple linear regression analysis. The results showed that non-performing loans and operating income operating costs had no effect on profitability at LPDs throughout Ubud district. Third party funds have a positive effect on profitability in LPDs throughout the Ubud district. Keywords: Non-Performing Loans; Third-Party Funds; Operating Expenses Operating Income; Profitability